ANALISIS KEBIJAKAN DAN KINERJA BPKAD DALAM MENINGKATKAN PENDAPATAN DAERAH KOTA BIMA - Sri Asmiatiningsih (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
Performance is the result of work that has a strong relationship with the organization's strategic objectives, customer satisfaction, and contributes to the economy. Basically, good performance is performance that follows the procedures or procedures according to established standards. Good employee performance will directly affect the performance of the institution, and to improve employee performance is certainly a time-consuming and long process. The performance of civil servants is an issue that is quite interesting to discuss, because it will be very useful for law enforcement which is also beneficial for the interests of individuals, society, the nation and the state. The roles and functions are clear that civil servants are very important. However, not all of these employees perform their roles and functions properly. Many employees work at their own pace, not paying attention to the results of their work. To create a good, professional and authoritative government, the influence of good civil servant performance will create a safe and comfortable atmosphere because the law is really made the commander. The Regional Asset Sector has the task of planning, coordinating, fostering, supervising and controlling and evaluating the asset administration sector, asset security sector and asset valuation sector.